Use of DSC in degree of conversion of dimethacrylate polymers: easier and faster than MIR technique - Alarcon, Rafael Turra [UNESP]; Gaglieri, Caroline [UNESP]; de Oliveira, Arthur Rossi [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2018)
This work aims to determine the degree of conversion of polymers obtained using diurethane dimethacrylate (UDMA) monomer by two different techniques: differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (MIR). The measurements were made in triplicate on both equipment, which resulted in average values for MIR 79.52 ± 3.57% (camphorquinone photoinitiator) and 78.15 ± 1.86% (fluorescein photoinitiator) and for DSC 80.85 ± 1.06 and 78.27 ± 1.71%. The DSC technique showed higher accuracy and lesser standard deviation. Furthermore, this technique is easier and faster than the MIR, and in situ polymerization is not necessary on the DSC equipment.
Keywords: Degree of conversion; Dimethacrylate; DSC; MIR; Photopolymerization; Techniques comparison